360° Video: Interview with Kiel Johnson, artist, Los Angeles, 18 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
Kiel Johnson is a Los Angeles-based artist, whose has found success in both the contemporary art scene and the commercial world. I've met Kiel many times - I took a group of Australian students to his studio in 2015, which Kiel followed-up with a visit to Australia in 2016. However, I had yet to do a StudioCrasher interview with him. In this three-part 360° interview, Kiel talks about how he got started, and where his work is heading now.